Decreased effector regulatory T cells and increased activated CD4+ T cells in premature ovarian insufficiency. (23rd April 2019) - Kobayashi, Mutsumi; Nakashima, Akitoshi; Yoshino, Osamu; Yoshie, Masanori; Ushijima, Akemi; Ito, Masami; Ono, Yosuke; Shima, Tomoko; Kawamura, Kazuhiro; Ishizuka, Bunpei; Saito, Shigeru
Abstract: Problem: Premature ovarian insufficiency (POI) is a clinical syndrome defined by the loss of ovarian activity before 40 years old. An autoimmune mechanism is suggested to be involved in the development of POI. Therefore, we examined the relationship between peripheral blood regulatory T (Treg) cells and autoantibodies in POI. Method of study: Thirty POI patients and 23 control women were enrolled in the study. Using flow cytometry, we measured the abundance of CD4 + T, CD4 + CD69 + T, CD8 + T, CD8 + CD69 + T, naive Treg, effector Treg, and FOXP3 + effector T cells in peripheral blood. Antinuclear and anti‐thyroglobulin antibody (Tg‐Ab) titers were measured in POI patients. Results: The number of CD4 + T or CD4 + CD69 + T cells was significantly higher in POI patients ( P = 0.045, and P = 0.030), and there were significantly fewer effector Treg cells in POI patients ( P = 0.016) than in the controls. There were significant negative correlations between effector Treg cells and Tg‐Abs ( r = −0.584, P = 0.0282), and between effector Treg cells and CD4 + CD69 + T cells ( r = −0.415, P = 0.0226) in POI patients. Conclusion: This is the first report of decreased numbers of effector Treg cells and increased CD4 + CD69 + activated T cells in peripheral blood in POI, suggesting that POI is an autoimmune disease.